Frequency of Breast Abscess Among Lactating Women in a Tertiary Care Hospital - Ahmed, Aniqa; Ghyasuddin, M; Ahmed, Hajrah Hilal; Ahmed, Rabia; Suchdev, Sunil Dut; Ghias, Nighat (Biological and Clinical Sciences Research Journal, 2025)
Breast abscess is a relatively common complication during lactation, often resulting in pain, discomfort, and interruption of breastfeeding. Prompt diagnosis and management are essential to prevent morbidity, yet its reported incidence varies across populations. Objective: To ascertain the frequency of breast abscess among lactating women presenting to a tertiary care hospital in Karachi, Pakistan. Methods: A descriptive cross-sectional study was conducted in the Department of Surgery at Kulsoombai Valika Social Security Hospital, Karachi, from July 2024 to December 2024. After obtaining ethical approval from the institutional review board, a total of 151 lactating women aged 20–40 years, presenting with a painful breast lump and swelling for at least 3 days, were enrolled through non-probability consecutive sampling. Data on sociodemographic variables, parity, and clinical presentation were collected. Descriptive statistics were used for baseline characteristics, and the Chi-square test was applied to evaluate associations between categorical variables. A p-value < 0.05 was considered statistically significant. Results: The mean duration of symptoms among participants was 8.2 ± 3.4 days. Breast abscess was diagnosed in 12% of the cases (n = 19). The occurrence of abscess did not show a statistically significant association with socioeconomic status (P = 0.744), with distribution as follows: poor (n = 6), middle class (n = 11), and rich (n = 2). Similarly, no significant relationship was observed between parity and abscess development (P = 0.626); 11 abscess cases were observed in women with parity ≤3 and 8 cases in those with parity >3. Conclusion: The study identified a 12% frequency of lactational breast abscess among the participants, which falls within the higher range reported in the literature. No significant association was observed with socioeconomic status or parity. Early detection and proper management are crucial to minimizing complications in lactating women.